Photochemistry and hydric responses of congeneric Croton species at restoration sites under dry season: implications for species selection - Rodrigues, Angélica L. [UNESP]; Bertholdi, Angelo A. S. [UNESP]; Mantoan, Luís Paulo B. [UNESP]; Vasconcellos, Gabriela M. [UNESP]; Almeida, Luiz Fernando R. [UNESP] (Springer Nature, 2019)
The success of the ecological restoration depends on the appropriate determination of species for implantation in restoration areas. The use of physiological performance as a criterion may help in the selection of species that are less susceptible to abiotic stress, and consequently experience a lower mortality rate. Species of the same genus can even exhibit differences in physiological responses to water deficiency. Thus, we hypothesize that congeneric species have different physiological responses to annual variation in water availability. Our objective was to determine which physiological parameters are more responsive to the differentiation of iso × anisohidric performances between the congeneric species Croton floribundus and Croton urucurana. In addition investigate whether these intrinsic differences are due to the influence of seasonality. We evaluated leaf water potential, stomatal conductance and chlorophyll a fluorescence of the two congeneric species in an ecological restoration area throughout the course of an entire year. Our results show that congeneric species exhibited similar partial isohydric performance, but they differ in stomatal conductance, predawn leaf water potential and photochemistry, especially in the activation of energy dissipation mechanisms via fluorescence due to the influence of seasonal changes, particularly the dry season. We conclude that using these species in the restoration of riparian forests would be advantageous due to their resistance to annual variation in water availability.
Keywords: Chlorophyll fluorescence; Croton; Seasonality; Stomatal conductance; Water potential